The Analysis of Cinematographic Elements as supporters of the Plot Twist in Movie, Coco Animation - Afandy Wicahyono (ROLLING, 2021)
In this era of globalization and digital as now this is one of the media that is still very interested in society is the film. Oneof the films that is still in demand either by adults or children is the animated film, one of which is Coco's animation. A nicemovie built on a plot that is not boring and more interesting if there is a twist plot element in it. Filmmaking takes a specialshooting technique or cinematography to have continuity and can be understood by film connoisseurs. The researchmethods used are qualitative descriptive. Researchers focused on the cinematography approach that would be applied toCoco's animated film with a duration of 109 minutes. The results of this study suggest that cinematography in particularframing (angle, type of shot, movement of the camera) in the sixth twist plot scene can support a twist plot. Not all have adefinite pattern in its use. Not all plot twist are built with camera movements, but are always supported with angle and typeof shot. The use of eye level in the animated film Coco proved to be able to support a plot twist. This is because the eye levelis capable of placing the audience as if it were among the characters in the animated film Coco. The Medium shot used inthe six scenes can support a plot twist in the animated film Coco because it is able to give curiosity, anxiety and surprise tothe audience through dialogue.